The Effect Of The Work Environment, Locus Of Control And Motivation On Employees Performance In Baznas Of South Sumatra Province - Aziz Septiatin; Yusiresita Pajaria; Fatimatuz Zuhro; Rosyada Rosyada (Jurnal I-Philanthropy, 2022)
The National Amil Zakat Agency (BAZNAS) is the official and only body established by the government which has the task and function of collecting and distributing zakat, infaq and alms (ZIS) at the national level. Human resources are one of the important factors for BAZNAS in carrying out its operational activities. This study aims to examine the effect of work environment, locus of control and motivation on employee performance. This type of research is quantitative research. The sampling technique used in this study is the saturated sampling technique, which is a sampling technique in which all members of the population are used as samples. In this study, researchers used a sample of 32 employees of BAZNAS, South Sumatra Province. The data analysis technique used is multiple regression analysis with the help of SPSS software. The results showed that the work environment had a positive and significant effect on employee performance, locus of control had a positive and significant effect on employee performance and motivation had a positive and significant effect on employee performance.Simultaneously the work environment, locus of control and motivation affect employee performance by 88.7%, while the remaining 11.3% is influenced by other variables that have not been studied or are not included in the regression in this study.